HGG-24. MOLECULAR, PATHOLOGICAL, RADIOLOGICAL AND IMMUNE PROFILING OF NON-BRAINSTEM PAEDIATRIC HIGH GRADE GLIOMA FROM THE HERBY PHASE II RANDOMISED TRIAL. Issue 2 (22nd June 2018) - Mackay, Alan; Burford, Anna; Molinari, Valeria; Jones, David; Izquierdo, Elisa; Brouwer-Visser, Juriaan; Giangaspero, Felice; Haberler, Christine; Pietsch, Torsten; Jacques, Thomas; Figarella-Branger, Dominique; Rodriguez, Daniel; et al.
Abstract: The HERBY trial was a phase-II open-label, randomised, multicentre trial evaluating bevacizumab in addition to temozolomide/radiotherapy in patients with newly-diagnosed non-brainstem high-grade glioma between the ages of 3-18 years. We collected specimens from 89/113 patients consenting to translational research, and carried out comprehensive molecular analysis integrated with pathology, radiology and immune profiling. 7/89 patients harboured H3F3A_G34R/V mutations (diffusely infiltrative with predominant deep left temporoparietal involvement), whilst 24/89 harboured H3F3A_K27M, both conferring a worse outcome. Of the latter, two patients had distinct, separate lesions in the thalamus and hypothalamus, whilst the remaining had symmetrical central thalamic and midbrain localization. Four older patients had tumours harbouring IDH1 mutations, whilst three younger patients had tumours which by methylation profiling resembled low grade lesions; both of these hemispheric subgroups had a significantly longer survival. Hypermutator tumours (driven by mismatch repair deficiency and somatic POLE / POLD1 mutations) and those biologically resembling pleomorphic xanthoastrocytoma (PXA-like, driven by BRAF_V600E or NF1 mutation) had an elevated immune response in the form of CD8-positive tumour infiltrating lymphocytes (p=0.0018), and had longer overall survival in the bevacizumab arm (p=0.0489). Histone H3 subgroups (hemispheric G34R/V and midline K27M) had a worse outcome and were immune cold. Although the experimental arm did not improve survival across the whole cohort, we identify disease subgroups with MAPK activation to harbour an enhanced immune response and derive benefit from the addition of bevacizumab to standard temozolomide/radiotherapy.